The Sixth-Century Samian Foot of 26.25 cm and Evolution of the Greek Linear Measure - Panchenko, Dmitri (Hyperboreus, 2017)
Herodotus (3. 60. 2) notes that both the height and the width of the Eupalinian aqueduct equal 8 feet. Modern measurement gives 2.10 m for both height and width. It follows that the sixth-century Samian foot was 26.25 cm, and there is much to support such a conclusion. However, a standard Greek foot was much longer. We are dealing here with two different systems. In the earlier one, the foot corresponds to the height of an average Greek man, and it measures a half of a cubit and a third of a pace. In the standard system, there is no integer number of feet in one pace, a foot corresponds to the height of exceptionally tall persons and it is in a ratio to a cubit of 2 : 3. The change was probably caused by the growing interest in athletic competitions. The stadiums were extended to accommodate more spectators, and, since each stadium was 600 feet long by deﬁnition, the foot was extended accordingly.